2003
DOI: 10.1289/ehp.5395
|View full text |Cite
|
Sign up to set email alerts
|

Power-line frequency electromagnetic fields do not induce changes in phosphorylation, localization, or expression of the 27-kilodalton heat shock protein in human keratinocytes.

Abstract: The linkage of the exposure to the power-line frequency (50-60 Hz) electromagnetic fields (EMF) with human cancers remains controversial after more than 10 years of study. The in vitro studies on the adverse effects of EMF on human cells have not yielded a clear conclusion. In this study, we investigated whether power-line frequency EMF could act as an environmental insult to invoke stress responses in human keratinocytes using the 27-kDa heat shock protein (HSP27) as a stress marker. After exposure to 1 gauss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
20
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 46 publications
4
20
0
Order By: Relevance
“…Heat shock proteins (HSP) are used as markers for cell responses against various stresses (13). HSP serve protective functions such as apoptosis and act as molecular chaperones during protein biosynthesis and tissue repair (14).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Heat shock proteins (HSP) are used as markers for cell responses against various stresses (13). HSP serve protective functions such as apoptosis and act as molecular chaperones during protein biosynthesis and tissue repair (14).…”
Section: Discussionmentioning
confidence: 99%
“…We used scanning electron microscopy (SEM) and characterized the expression of HSP27 mRNA, which is present in osteoblasts lining newly-formed bone. HSP27 mRNA helps repair denatured proteins or promote their degradation after various types of stress (12)(13)(14). Moreover, expression of type I collagen and alkaline phosphatase (ALP) mRNAs was also evaluated using reverse transcription polymerase chain reaction (RT-PCR) (15)(16).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of HSP16, HSP27 and HSP70 has been reported to be increased at magnetic-field strengths ranging from 8 Tt o 500 mT (15)(16)(17). However, other studies have reported that magnetic-field strengths of a similar range (6.3 T-50 mT) have no effect on heat-shock protein expression in a variety of biological models (18)(19)(20)(21). The physiological implications of field-induced heat-shock protein expression are unknown, but they could range from therapeutically beneficial to detrimental.…”
Section: Introductionmentioning
confidence: 99%
“…The studies conducted on human keratinocytes subjected to 100 T showed that power line electromagnetic fields cannot induce changes in phosphorylation, localization or expression of the HSP 27 [43,44]. However, the cultures of human endothelial cell lines exposed to mobile phone radiation (RF-EMF) showed an increased expression and phosphorylation of HSP 27.…”
Section: Discussionmentioning
confidence: 99%